P1583 Usefulness of remote intrathoracic impedance alerts for echo-guided CRT optimization. (17th January 2020) - Appignani, M; Salvatore, T; Di Girolamo, E
Abstract: Background: Cardiac resynchronisation therapy (CRT) is a strong recommendation in heart failure (HF) patients having sinus rhythm, left bundle branch block, QRS duration ≥ 120 ms and left ventricular (LV) ejection fraction (EF) ≤ 35%, despite optimized medication. Echocardiographic parameters still have a controversial role in the selection of patients ongoing CRT, and no single parameter is recommended to identify a positive CRT response. Even their role in the management after implantation remains still troubleshooting. Atrioventricular (AV) and interventricular (VV) delay reprogramming could be a variable that may influence CRT outcome and, although a systematic AV and VV optimization is not required, it could be useful in selected patients. Remote monitoring networks allow HF patients having a CRT device to be constantly monitored, and notifications of some intrathoracic impedance indexes, may be helpful in the management of HF patients. Purpose: To evaluate the usefulness of intrathoracic impedance notifications in the selection of HF patients to have echo-guided AV and/or VV delays optimization, the following study was undertaken. Methods: 27 CRT patients having an intrathoracic impedance enabled remote monitoring, with at least one impedance notification during the first six months from implantation, were considered for study. The primary endpoint was a composite of improvement in NYHA functional class and EF, reduction of LV end-systolic volume and rehospitalization for decompensated HF. Secondary endpoint was the effectiveness of echo-guided dealys optimization based on intrathoracic impedance alerts. The AV delay optimization was mainly driven by mitral inflow pattern, whereas VV delay optimization was guided by the assessment of LV synchrony using color Tissue Doppler Imaging (TDI). Patients were weekle evaluated through remote monitoring network over a six-month follow-up. LVEF and LV end-systolic volume were determind at baseline and after six months. Results: After the six-month follow-up, an improvement of at least 1 NYHA functional class was obtained in 23 patients (85%), while 2 patients (7.4%) experienced an improvement of two NYHA classes. In 21 Patients (77.7%) LVEF increased at least 5%. Optimization was associated with an average 11.9 ± 6.4% increas in EF, from a mean baseline of 28.2 ± 3.2% to 37.8 ±6.2%. End-systolic volume decreased from 161.56 ± 9.87 ml to 143.22 ± 15.83 ml. Among the 27 patients with impedance alerts at baseline, only 6 (22.2%) reported new notifications during follow-up, with a significant reduction (p < 0.03) after optimization. Conclusions: Intrathoracic impedance monitoring improved the selection of non responders feasible to have echo-guided AV and/or VV delays optimization. Functional status and LVEF increased. Although time-consuming, this multidisciplinary network may increase close cooperation between electrophysiologist and HF physicians to better manage HF patients having a CRT system implanted.